Fine mapping of the antigenic epitopes of the Gc protein of Guertu virus - Yusufu, Meilipaiti; Abula, Ayipairi; Jiang, Boyong; Zhumabai, Jiayinaguli; Deng, Fei; Li, Yijie; Zhang, Yujiang; Ding, Juntao; Sun, Surong (PloS one, 2022)
Guertu virus (GTV), a newly discovered member of the genus Banyangvirus in the family Phenuiviridae , poses a potential health threat to humans and animals. The viral glycoprotein (GP) binds to host cell receptors to induce a neutralizing immune response in the host. Therefore, identification of the B-cell epitopes (BCEs) in the immunodominant region of the GTV Gc protein is important for the elucidation of the virus–host cell interactions and the development of GTV epitope assays and vaccines. In this study, an improved overlapping biosynthetic peptide method and rabbit anti-GTV Gc polyclonal antibodies were used for fine mapping of the minimal motifs of linear BCEs of the GTV Gc protein. Thirteen BCE motifs were identified from eleven positive 16mer-peptides, namely EGc1 ( 19 KVCATTGRA 27 ), EGc2 ( 58 KKINLKCKK 66 ), EGc3 ( 68 SSYYVPDA 75 ), EGc4 ( 75 ARSRCTSVRR 84 ), EGc5 ( 79 CTSVRRCRWA 88 ), EGc6 ( 90 DCQSGCPS 97 ), EGc7 ( 96 PSHFTSNS 103 ), EGc8 ( 115 AGLGFSG 121 ), EGc9 ( 148 ENPHGVI 154 ), EGc10 ( 179 KVFHPMS 185 ), EGc11 ( 230 QAGMGVVG 237 ), EGc12 ( 303 RSHDSQGKIS 312 ), and EGc13 ( 430 DIPRFV 435 ). Of these, 7 could be recognized by GTV IgG-positive sheep sera. Three-dimensional structural analysis revealed that all 13 BCEs were present on the surface of the Gc protein. Sequence alignment of the 13 BCEs against homologous proteins from 10 closely related strains of severe fever with thrombocytopenia syndrome virus from different geographical regions revealed that the amino acid sequences of EGc4, EGc5, EGc8, EGc11, and EGc12 were highly conserved, with 100% similarity. The remaining 8 epitopes (EGc1, EGc2, EGc3, EGc6, EGc7, EGc9, EGc10, and EGc13) showed high sequence similarity in the range of 71.43%–87.50%. These 13 BCEs of the GTV Gc protein provide a molecular foundation for future studies of the immunological properties of GTV glycoproteins and the development of GTV multi-epitope assays and vaccines.